Growth responses of Skeletonema marinoi-dohrnii complex and Chattonella marina under different nitric oxide (NO) supply rates - Shigenobu Takeda (PANGAEA, 2025)
Growth responses of Skeletonema marinoi-dohrnii complex and Chattonella marina isolated from Japanese coastal waters were monitored under different nitric oxide (NO) supply rates using a variable-volume repeated fed-batch (VRFB) culture system. Culture experiments for S. marinoi-dohrnii complex were performed at three NO levels: low, medium, and high. The average NO supply rates at the low, medium, and high NO levels were 1.4, 5.4, and 28 pM/s, respectively. In the C. marina culture experiments, 2.5 pM/s NO supply rate (low-medium treatment) was used instead of 28 pM/s. In both experiments, a treatment feeding deoxygenated f/2 medium without NO was used as the control. The S. marinoi-dohrnii complex and C. marina were cultured in the VRFB culture system for 3 days. To examine the recovery from NO-induced growth inhibition, phytoplankton growth was monitored for several days after the termination of 3-day NO supply.